Decision Science. - Van Ackere, Ann (Taylor and Francis, 2017)
"This title was first published in 2000. This text is part of the "International Library of Management", which aims to present a comprehensive core reference series comprised of significant and influencial articles by the authorities in the management studies field. The collection of essays is both international and interdisciplinary in scope and aims to provide an entry point for investigating the myriad of study within the discipline."--Provided by publisher.
Keywords: Decision making.